Triglyceride-Glucose Index as a Predictor of Diabetic Foot Ulcer Severity in Type 2 Diabetes Mellitus: Cross-Sectional Study - Istiqomah; Fauzia Noor Liani; Mohammad Bakhriansyah (‎ InaJEMD - Indonesian Journal of Endocrinology Metabolic and Diabetes, 2025)
Diabetic foot ulcers are a complication of type 2 diabetes mellitus that has a high global prevalence. Insulin resistance in type 2 DM patients tends to cause chronic wounds and can delay wound healing. TyG index is currently used as a surrogate biomarker to evaluate insulin resistance because it is easy to perform and low cost. Analytic observational research with a cross-sectional approach at Diabetic Foot Poly Ulin Hospital Banjarmasin. The study sample was all patients diagnosed with type 2 DM and undergoing wound care at the Diabetic Foot Polyclinic of Ulin Hospital Banjarmasin starting in December 2024 who met the inclusion and exclusion criteria with a total of at least 74 people. Data analysis was performed with a simple binomial logistic regression test to estimate crude Prevalence Odds Ratio (POR) with 95% confidence intervals, and multiple binomial logistic regression tests were performed to estimate adjusted POR and 95%CIs. Compared with the lowest one-third TyG Index score, study subjects with the middle one-third TyG Index score were associated with a lower risk of severe diabetic foot ulcer incidence by 85.9% (Adj POR 0.141, 95% CI: 0.011-1.802). Subjects with the highest third TyG Index value were also associated with a lower risk of diabetic foot ulcer incidence of 87.1% (Adj POR 0.129, 95%CI: 0.008-1.959). The mean value of TyG Index+SD was 4.8872 + 0.4230 at severe foot ulcers. TyG index is not a predictive factor for the severity of diabetic foot ulcers in type 2 DM patients at the Diabetic Foot Clinic of Ulin Hospital Banjarmasin (p>0.05).